The effect of governance on entrepreneurship: From all income economies perspective - Mekonnen Bogale Abegaz; Kenenisa Lemi Debela; Reta Megersa Hundie (Journal of Innovation and Entrepreneurship, 2023)
The purpose of this study is to analyze the effect of governance indicators on Entrepreneurship. Explanatory research design with Pearson correlation and multiple linear regression models were applied. Five-year World Bank data (2014-2018) of 126 countries from all economic development levels were used. Worldwide governance indicators considered are voice and accountability, political stability, government effectiveness, regulatory quality, rule of law, and corruption control. Gross net income was taken as a control variable. To measure entrepreneurship, the number of formally registered limited liability businesses as a percentage of the working-age population, was used. To make highly skewed time series data of dependent variable (entrepreneurship) closer to normal, logarithmic transformation was made and heteroscedasticity of residuals was checked. The finding of Pearson correlation shows that there are moderate to strong significant correlations (0.466 ≤ r ≤ 0.806, p < 0.01) between predictors and the outcome variable. Predictor variables have moderate to very strong correlation among each other (0.506 ≤ r ≤ 0.956, p < 0.01). Regression analysis was computed after two highly collinear variables were dropped from the model using the variance inflation factor (VIF) test. The study found that the remaining four independent variables and the control variable predict 71.5% of the variance in the outcome variable. Except for voice and accountability, all predictors have their own statistically significant influence on entrepreneurship. Thus, working on each predictor up to the standard application can bring incremental changes in new business formation and entry. The researchers believe that this study is of significant interest to policymakers, program developers, entrepreneurs, analysis, and supporters, since it provides useful insight on how governance indicators influence entrepreneurship.
Keywords: 650; Corruption control; Entrepreneurship; Governance; Gross net income; Political stability; Regulatory quality; Voice and accountability